Prenatally Acquired Vitamin A Deficiency Alters Innate Immune Responses to Human Rotavirus in a Gnotobiotic Pig Model - Vlasova, Anastasia N; Chattha, Kuldeep S; Kandasamy, Sukumar; Siegismund, Christine S; Saif, Linda J (The Journal of immunology (1950), 2013)
We examined how prenatally acquired vitamin A deficiency (VAD) modulates innate immune responses and human rotavirus (HRV) vaccine efficacy in a gnotobiotic (Gn) piglet model of HRV diarrhea. The VAD and vitamin A–sufficient (VAS) Gn pigs were vaccinated with attenuated HRV (AttHRV) with or without concurrent oral vitamin A supplementation (100,000 IU) and challenged with virulent HRV (VirHRV). Regardless of vaccination status, the numbers of conventional and plasmacytoid dendritic cells (cDCs and pDCs) were higher in VAD piglets prechallenge, but decreased substantially postchallenge as compared with VAS pigs. We observed significantly higher frequency of CD103 (integrin αEβ7) expressing DCs in VAS versus VAD piglets postchallenge, indicating that VAD may interfere with homing (including intestinal) phenotype acquisition. Post-VirHRV challenge, we observed longer and more pronounced diarrhea and higher VirHRV fecal titers in nonvaccinated VAD piglets. Consistent with higher VirHRV shedding titers, higher IFN-α levels were induced in control VAD versus VAS piglet sera at postchallenge day 2. Ex vivo HRV-stimulated mononuclear cells (MNCs) isolated from spleen and blood of VAD pigs prechallenge also produced more IFN-α. In contrast, at postchallenge day 10, we observed reduced IFN-α levels in VAD pigs that coincided with decreased TLR3+ MNC frequencies. Numbers of necrotic MNCs were higher in VAD pigs in spleen (coincident with splenomegaly in other VAD animals) prechallenge and intestinal tissues (coincident with higher VirHRV induced intestinal damage) postchallenge. Thus, prenatal VAD caused an imbalance in innate immune responses and exacerbated VirHRV infection, whereas vitamin A supplementation failed to compensate for these VAD effects.